Peranan Komisi Pemilihan Umum dalam Melaksanakan Pendidikan Politik bagi Pemili Pemula di Kabupaten Gowa - Rismawati Rismawati; Mardiana Mardiana (Universitas of Muhammadiyah Makassar, 2018)
This study aims to determine the role of Gowa Regency KPU in carrying out political education for beginner voters in Gowa Regency, to find out the supporting factors of Gowa Regency KPU in carrying out political education for beginner voters in Gowa Regency and to know the inhibiting factors of Gowa Regency KPU in carrying out political education for beginner voters in Gowa Regency. The type of this research is descriptive qualitative research and the data analysis technique is done in qualitative descriptive. The results of this study prove that the Role of the Gowa Regency Election Commission in Implementing Political Education for Beginners Election in Gowa Regency is 1) Conducting Socialization to Beginner Voters with a road to school program and casual walking activities, (2) Information Dissemination through Tools Props, (3) Socialization through mass media, such as: Radio and newspapers, (4) Democracy Volunteer Program (Relations), (5) Mobile Car Socialization or methodology, (6) Workshop and (7) Writing Competition Student Essays and Debates. Gowa Regency KPU in implementing political education for voters is influenced by two factors, namely supporting and inhibiting factors. Supporting factors (1) Adequate human resources in Gowa Regency KPU and (2) Collaboration with communities and educational institutions. While the inhibiting factors are (1) Geographical location of the socialization location, (2) Lack of awareness of political parties, and (3) Budget that is still lacking from the government.Keywords : Role of the Election Commission, Political Education and Beginner Voters.